(untitled) (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this study is to find out and see the influence of transparency and community participation on the Management of the APBDes. Method - The population of this study is 15 villages in North Indralaya District. The sample consisted of 90 respondents who were selected using saturated sampling techniques and using primary data through questionnaires and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). Main Findings - The results of this study state that all independent variables, namely transparency and community participation, have a positive and significant effect on the Management Management of the APBDes. The higher the transparency and also community participation, the better the Management Management of the APBDes. This emphasizes the importance of open village governance and actively involving the community. Theory and Practical Implications - The implications of this research are considered and referenced for village governments in improving the village fund management system to be more open and involve the community Novelty - This study uses PLS-SEM, which allows for a more complex and in-depth analysis of the research results but also adds to the understanding of how Transparency and Community Participation collectively affect the Management of Village Revenue and Expenditure Budgets